Attentional dysfunction and recovery in concussion: effects on the P300m and contingent magnetic variation. (21st March 2018) - Petley, Lauren; Bardouille, Tim; Chiasson, Darrell; Froese, Patrick; Patterson, Steve; Newman, Aaron; Omisade, Antonina; Beyea, Steven
ABSTRACT: Primary objective : To examine the effect of concussion on indices of attention using magnetoencephalography. Methods and procedures : Thirteen patients were recruited from the emergency department and scanned within 3–6 days of injury. Five returned for follow-up scans one and three months post-injury. Thirteen healthy controls also completed testing. During MEG acquisition, participants performed the Attention Network Test (ANT). Cognitive evoked responses to this task include a cue-evoked P300m, a contingent magnetic variation (CMV) and a target-evoked P300m. The Rivermead Postconcussion Symptom Questionnaire and Sport Concussion Assessment Tool (SCAT3) were administered in all sessions. Results : Patients suffering from concussion had slower response times and benefitted more from spatial cues than did controls. Global activation for all three evoked responses was lower for patients than controls. In a small sample of patients who returned for follow-up, the CMV and target P300m improved with recovery. Conclusions : MEG-evoked responses to the ANT reveal neurophysiological evidence of attentional dysfunction within days of injury. A pattern of improvement was also observed over the course of three months for the P300m, while behavioural performance did not change significantly. Further development of this method may yield a useful adjunct to neurological examination for concussion diagnosis and monitoring.